Influence of Shareholders' Activism and Firm-level Variables on the Corporate Governance Quality in India. Issue 2 (December 2016) - Bhandari, Varun; Arora, Ashima
Abstract: Corporate governance (CG) gained widespread prominence as a medium for boosting corporate performance especially after the financial crisis of 2008. With limited empirical work on factors influencing the CG quality (CGQ), this article focuses on the construction of the CG Index (CGI) by considering a total of 64 attributes encapsulated in five sub-indices followed by the investigation of effect of shareholder activism and firm-level variables on it. The estimations are based on companies listed in S&P CNX NIFTY Index from the financial year 2008–2013. The examination of results relays that both shareholder activism and firm-level variables have a significant impact on the CGQ of the firms. The significant impact of Disclosure and Board Index on the performance of firms emphasised the importance of disclosure norms in driving the performance by improving investor perceptions through higher transparency. And active board contributes in dispelling agency and managerial issues assisting in improving firm's value. Our findings imply that shareholder activism and firm-level variables help in bolstering the quality of CG. Large concentrated holdings limit the power in few hands that deter the use of effective shareholder activism and thus should be reduced to enhance the quality of governance. The policymakers and regulators are needed to pressurise institutional investors for active participation in the companies' routine decisions to increase vigilance regarding CG issues.